(untitled) (Euro-Asia Conferences, 2021)
Neurosonography (NSG) is currently the primary screening method of research, due to its ease of implementation and relative availability.Neurosonography is a method of two-dimensional ultrasound examination of the anatomical structures of the brain, which uses the property of sound to be reflected from the boundaries of tissue structures. Acoustic windows: large and small fontanelles, defects in the bones of the skull, enlarged sutures, foramen magnum in newborns. The method is non-invasive, does not require preliminary preparation and allows tracing the dynamics of the pathological process in real time. The image is presented on the monitor screen in the form of signals of hyper- and hypoechoic density. The method is used for prenatal and postnatal diagnostics of cerebral malformations; hypoxic-ischemic, hemorrhagic, traumatic and inflammatory brain injuries and their consequences; tumors, ventriculomegaly. A sign of cerebral ischemia is the presence of diffuse hyperechoic foci, more often in the periventricular region, expansion of the interhemispheric groove, subarachnoid spaces, symmetrical expansion of the ventricular system. Intraventricular hemorrhage (IVH) and parenchymal - hyperechoic formations with clear contours, located intraventricular, subcortical or cortical.It is of great diagnostic value in assessing the severity of DIE in newborns. The greatest diagnostic value of NSH is manifested in the diagnosis of congenital malformations of the central nervous system, internal hydrocephalus, periventricular hemorrhage, periventricular leukomalacia at the stage of cyst formation. To a large extent, the specificity and reliability of the information received depends on the quality of the equipment and the experience of the physician-researcher. The timing of the study is of no small importance, since some variants of damage to the central nervous system of newborns (such as the formation of cysts) can most accurately be diagnosed by the end of 2-3 weeks. life. About 20% of negative results of NSH can be explained by this. Despite the widespread use of NSH, the results of researchers are not unambiguous